Mechanical behaviour of soils under environmentally induced cyclic loads - Wood, David Muir; Prisco, Claudio (CISM Courses and Lectures, 2012)
The book gives a comprehensive description of the mechanical response of soils (granular and cohesive materials) under cyclic loading. It provides the geotechnical engineer with the theoretical and analytical tools necessary for the evaluation of settlements developng with time under cyclic, einvironmentally idncued loads (such as wave motion, wind actions, water table level variation) and their consequences for the serviceability and durability of structures such as the shallow or deep foundations used in offshore engineering, caisson beakwaters, ballast and airport pavements and also to interpret monitoring data, obtained from both natural and artificial slopes and earth embankments, for the purposes of risk assessment and mitigation.